Analisis Terhadap Langkah-Langkah dan Teknik yang Efektif dalam Pembelajaran Pendidikan Agama Islam: Analysis of Effective Steps and Techniques in Learning Islamic Religious Education - Satya Nur Pamungkas, Satya; Hadziq Ubaidilbarr, M.; Sulistiani, Mia; Nasikhin (CV. Kalimasada Group, 2023)
This study aims to analyze effective steps and techniques in Islamic Religious Education (PAI) learning to ensure the achievement of educational goals. It is crucial for PAI teachers to design lessons, set objectives, develop learning evaluations, and use strategies that can improve and shape students' character. Integrated curriculum development and holistic learning approaches are also necessary. This research employs a library research method by gathering data from books, journals, and documents. The study focuses on: 1) The essence of PAI learning, 2) Analysis of steps in PAI learning, and 3) Effective techniques used in PAI learning. This analysis helps identify effective teaching strategies to enhance students' understanding of religious values, facilitate the internalization of Islamic teachings, and shape students' character. Additionally, it supports the development of innovative approaches, ensuring that PAI learning becomes a more impactful and meaningful experience for students.